A framework to classify error in animal-borne technologies - Burns, Zackory T.; van Loon, E. Emiel (Frontiers in Ecology and Evolution, 2015)
The deployment of novel, innovative, and increasingly miniaturized devices on fauna, especially otherwise difficult to observe taxa, to collect data has steadily increased. Yet, every animal-borne technology has its shortcomings, such as limitations in its precision or accuracy. These shortcomings, here labelled as ‘error’, are not yet studied systematically and a framework to identify and classify error does not exist. Here, we propose a classification scheme to synthesize error across technologies, discussing basic physical properties used by a technology to collect data, conversion of raw data into useful variables, and subjectivity in the parameters chosen. In addition, we outline a four-step framework to quantify error in animal-borne devices: to know, to identify, to evaluate, and to store. Both the classification scheme and framework are theoretical in nature. However, since mitigating error is essential to answer many biological questions, we believe they will be operationalized and facilitate future work to determine and quantify error in animal-borne technologies. Moreover, increasing the transparency of error will ensure the technique used to collect data moderates the biological questions and conclusions.